2019
DOI: 10.7567/1347-4065/ab4681
|View full text |Cite
|
Sign up to set email alerts
|

Local structural analysis of Pb(Fe1/2Nb1/2)O3 multiferroic material using X-ray fluorescence holography

Abstract: We performed X-ray fluorescence holography measurements on a Pb(Fe 1/2 Nb 1/2 )O 3 (PFN) multiferroic material in order to investigate the temperature dependence of three dimensional local structure around Fe atoms. It was found that the atomic image intensity of the nearest neighbor Pb atom abruptly decreases when the temperature becomes lower than the Néel temperature (T N ) of about 150 K, while the intensity of the atomic image at nearest Fe/Nb position remains almost unchanged. These observations show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…For the crystal structure analysis, we use white neutron holography, a kind of atomic resolution holography that can directly reveal a three-dimensional local structure around a dopant without any structure model. The white neutron holography exhibits higher sensitivity to light elements, such as hydrogen, B, and oxygen, compared with X-ray fluorescence holography and photoelectron holography. Thanks to the white neutron holography, we successfully revealed that the B-doping site in the Mg 2 Si SCs is the Mg site . Similarly, we determine the B-doping site in the Mg 2 Sn SCs using the white neutron holography.…”
Section: Introductionmentioning
confidence: 91%
“…For the crystal structure analysis, we use white neutron holography, a kind of atomic resolution holography that can directly reveal a three-dimensional local structure around a dopant without any structure model. The white neutron holography exhibits higher sensitivity to light elements, such as hydrogen, B, and oxygen, compared with X-ray fluorescence holography and photoelectron holography. Thanks to the white neutron holography, we successfully revealed that the B-doping site in the Mg 2 Si SCs is the Mg site . Similarly, we determine the B-doping site in the Mg 2 Sn SCs using the white neutron holography.…”
Section: Introductionmentioning
confidence: 91%
“…In 2017, Stellhorn et al [45] used XFH to measure the three-dimensional structure around the Fe and Ni atoms in Fe 65 Ni 35 Invar alloy. In 2019, Kimura et al [46] used XFH to measure the three-dimensional structure around the Fe atoms in Pb(Fe 1/2 Nb 1/2 )O 3 (PFN) multiferroic material at different temperatures to study the relationship between atomic images and temperature. In 2020, Ang et al [47] measured the original and irradiated κ-(BEDT-TTF) 2 Cu[N(CN) 2 ]Br crystals with XFH.…”
Section: Applicationsmentioning
confidence: 99%
“…Later the involvement of Pb ions into the superexchange interaction between Fe ions in PFN was confirmed by X-ray fluorescence holography measurements. 37 Recently, a possibility of similar nontrivial magnetic superexchange between Fe 3þ ions in BiFeO 3 via the empty 6p-states of Bi 3þ was predicted theoretically. 38 However, this mechanism of superexchange seems to become noticeable only at high enough dilution of the Fe-sublattice, i.e., in solid solutions.…”
Section: Introductionmentioning
confidence: 99%